Thick film resistor composition and thick film resistor paste containing same

By using a composition containing needle anatase powder and glass glaze gold in thick film resistors, the problem of insufficient resistance value adjustment in the prior art is solved, and a larger resistance change range and higher accuracy resistance value adjustment is achieved, which significantly improves the efficiency of industrial applications.

JP7664685B2Active Publication Date: 2025-04-18SUMITOMO METAL MINING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020099523
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-08
Publication Date
2025-04-18
Estimated Expiration
2040-06-08

AI Technical Summary

Technical Problem

When the prior art adjusts the resistance value of a thick film resistor through the pulse trimming method, the resistance value adjustment is not sufficient and it is difficult to meet the higher accuracy requirements.

Method used

Thick film resistor compositions containing glass glaze gold and acicular anatase powder are used, in which the needle particles of the anatase powder have a smaller maximum cross-sectional width (100 nm or less) and a higher aspect ratio (1.5 or more), and the softening point of glass glaze gold is determined by differential thermal thermal analysis to be 600°C or more.

Benefits of technology

Through the use of such a composition, the adjustment range and accuracy of the resistance value can be significantly improved, the adjustment process of the resistance value is simplified, and the efficiency of industrial applications is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664685000003
    Figure 0007664685000003
  • Figure 0007664685000001
    Figure 0007664685000001
  • Figure 0007664685000002
    Figure 0007664685000002
Patent Text Reader

Abstract

To provide a thick film resistor composition capable of efficiently adjusting a resistance value of a thick film resistor by a pulse trimming method.SOLUTION: A thick film resistor composition includes a glass frit and ruthenium compound powder 1, and the ruthenium compound powder is needle-like particles, and the maximum width φ1 of the cross section of the ruthenium compound powder perpendicular to the particle length L direction of the needle-like particles is 100 nm or less, and the aspect ratio expressed by the formula of "particle length / maximum width" obtained from the particle length L and the maximum width φ1 is 1.5 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thick film resistor composition for use in producing chip resistors, thick film resistor substrates, thick film resistor heaters, and the like. [Background technology]

[0002] Generally, chip resistors, thick film resistors, thick film resistor heaters, etc. use, for example, an alumina substrate as the substrate, thick film electrodes as the electrodes, and thick film or thin film resistors as the resistors. There are various types of these resistors depending on their applications and characteristics, and resistor-related parts are rapidly becoming smaller as devices become smaller.

[0003] Furthermore, there are various types of chip resistors with different characteristics, such as surge resistance, trimmable products, and high precision products. The resistance value of chip resistors is generally adjusted by laser trimming, which removes part of the thick-film resistor with a laser beam. However, adjusting the resistance value by laser trimming leaves a trace on the surface of the thick-film resistor. Therefore, there are methods for adjusting the resistance value of thick-film resistors that do not leave traces, such as irradiating the thick-film resistor with a laser beam to change its characteristics and lowering its resistance value, or applying a pulse voltage to the thick-film resistor to lower its resistance value.

[0004] These methods of causing characteristic changes using laser light and of lowering the resistance value by applying a pulse voltage to a thick-film resistor are adjustment methods that utilize the fact that the resistance value can be lowered by applying laser light or a pulse voltage of an energy level that does not physically damage the appearance of the thick-film resistor. Among these, a method of applying a high voltage pulse to a thick-film resistor to reduce its resistance value is known as a pulse trimming method. Patent Documents 1 and 2 disclose techniques relating to the pulse trimming method. It is believed that with the further miniaturization of components in the future, such a method of adjusting resistance value without physically destroying anything will become even more necessary. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2002-067366 A [Patent Document 2] JP 2002-127483 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, depending on the composition of the thick-film resistor composition, even if an attempt is made to adjust the resistance value of the resulting thick-film resistor by pulse trimming, the adjustment of the resistance value, i.e., the change in the resistance value, may not be sufficient. In view of the above circumstances, an object of the present embodiment is to provide a thick-film resistor composition that allows the resistance value of a thick-film resistor to be efficiently adjusted by a pulse trimming method. [Means for solving the problem]

[0007] The first invention of the present invention comprises glass frit and a ruthenium compound powder, the ruthenium compound powder being acicular particles, the maximum width of a cross section perpendicular to the particle length direction being 100 nm or less, and the aspect ratio calculated from the particle length and the maximum width, expressed by the formula "particle length (L) / maximum width (φ1)", is 1.5 or more. , 5.0 or less The glass frit is heated in air at a rate of 10°C / min by differential thermal analysis (TG-DTA), and the softening point, which is the temperature at which the next differential thermal curve on the higher side decreases from the temperature at which the lowest differential thermal curve decreases, is 600°C or more and 900°C or more. below The thick film resistor composition is characterized in that

[0008] The present invention 2 The invention is First invention The thick-film resistor composition is characterized in that the ruthenium compound powder in the above is ruthenium dioxide powder.

[0009] The present invention Third The invention is First or second invention and a vehicle in which a resin is dissolved in an organic solvent. Effect of the Invention

[0010] According to this embodiment, a resistor having a large resistance change range when the resistance value is adjusted by a pulse can be easily obtained, which contributes greatly to improving the adjustment work and provides a significant industrial effect. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is an explanatory diagram of the form of a ruthenium compound powder according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The thick-film resistor composition according to the present embodiment is characterized in that it contains glass frit and a conductive ruthenium compound powder, and the ruthenium compound powder is acicular. Furthermore, the ruthenium compound powder is preferably ruthenium dioxide powder.

[0013] The thick film resistor composition can be used to obtain a thick film resistor paste by kneading the thick film resistor composition with an organic vehicle described below. The thick film resistor paste thus obtained is printed on the surface of a ceramic substrate such as an alumina substrate to form a printed film containing the thick film resistor composition, which is then fired to obtain a thick film resistor. Each component will be described below.

[0014] [Glass frit] The composition and manufacturing method of the glass frit are not particularly limited. Lead-containing lead aluminoborosilicate is often used as the glass frit for thick-film resistor compositions, but other lead-free compositions such as zinc borosilicate, calcium borosilicate, and barium borosilicate are also used. In recent years, it has become desirable to use lead-free glass from the viewpoint of environmental protection.

[0015] As described above, for example, the glass of the glass frit can be one or more selected from lead aluminoborosilicate glass, zinc borosilicate glass, calcium borosilicate glass, and barium borosilicate glass. Also, lead-free glass, for example, one or more selected from zinc borosilicate glass, calcium borosilicate glass, and barium borosilicate glass, can be used.

[0016] The SiO2 component contained in the glass frit constitutes the glass skeleton, while PbO, B2O3, and RO (R is an alkaline earth element) adjust the melting property of the glass. Furthermore, for the purpose of adjusting the weather resistance of the glass and the fluidity during firing, one or more types selected from Al2O3, ZrO2, TiO2, SnO2, ZnO, Li2O, Na2O, K2O, etc. can be used. Al2O3 tends to suppress phase separation of the glass, ZrO2 and TiO2 improve the weather resistance of the glass, and SnO2, ZnO, Li2O, Na2O, K2O, etc. work to increase the fluidity of the glass.

[0017] The glasses are generally produced by mixing the desired components or their precursors in the desired formulation, melting the resulting mixture, and quenching it. The melting temperature is not particularly limited, but is, for example, about 1400° C. Rapid cooling is often performed by placing the molten material in cold water or by passing it over a cold belt. The glass is ground to the desired particle size using a ball mill, a vibration mill, a planetary mill, a bead mill, or the like.

[0018] The particle size of the glass frit is not limited, but the 50% volume cumulative particle size measured by a particle size distribution analyzer using laser diffraction is preferably 5 μm or less, and more preferably 3 μm or less. Thus, if the particle size of the glass frit is too large, the sheet resistance value of the fired thick film resistor is low, but the variation in the sheet resistance value increases, resulting in a decrease in yield. Furthermore, there is a high possibility of problems such as a decrease in load characteristics. Therefore, from the viewpoint of sufficiently increasing the yield and improving the load characteristics, it is preferable that the 50% volume cumulative particle size of the glass particles used is 5 μm or less. Incidentally, if the particle size of the glass frit is made too small, the productivity may decrease and the inclusion of impurities may increase, so the 50% volume cumulative particle size of the glass frit is preferably 0.5 μm or more.

[0019] The softening point is a measure that affects the fluidity of glass during firing. In general, the temperature at which a composition for a thick-film resistor is fired during production of a thick-film resistor is 800° C. or higher and 900° C. or lower. In this way, when the firing temperature of the composition for a thick film resistor when manufacturing a thick film resistor is 800°C or higher and 900°C or lower, the softening point of the glass used in the composition for a thick film resistor of this embodiment is preferably 600°C or higher and 900°C or lower. Also, a glass frit having a softening point of 600° C. or more and 800° C. or less can be mixed with a glass frit having a higher softening point. The softening point herein is the temperature at which the next differential thermal curve on the higher side decreases compared to the temperature at which the lowest differential thermal curve decreases when a glass is heated in air at a rate of 10°C / min by differential thermal analysis (TG-DTA).

[0020] The thick film resistor is obtained by firing the thick film resistor composition. The firing temperature for obtaining the thick film resistor is 800°C to 900°C as described below, and the glass frit melts during the firing process, and each particle of the glass frit fuses to form a glass matrix. Each particle of the ruthenium compound powder constituting the thick film resistor does not melt during the firing process like the glass frit. And the thick film resistor obtained by firing the thick film resistor composition has a conductive network of ruthenium compound particles held and formed by the glass matrix as a component.

[0021] [Ruthenium compound powder] The ruthenium compound powder in the thick film resistor composition functions as a conductive component. As the ruthenium compound powder, a ruthenium composite oxide powder such as a ruthenium dioxide powder, a lead ruthenate powder, or a strontium ruthenate powder can be used.

[0022] In addition, the ruthenium compound powder used in this embodiment has the form of straight acicular particles as shown in Figure 1, and the maximum length of the straight acicular particles, that is, the particle length L, and the maximum width φ1 of a cross section perpendicular to the direction of the particle length are 100 nm or less, and the aspect ratio of the straight acicular particles calculated from the particle length L and the maximum width φ1 of the cross section by the formula "particle length L / maximum width of cross section φ1" is 1.5 or more, and preferably 5.0 or less.

[0023] The thick film resistor comprises a conductive network of needle-shaped particles of a ruthenium compound powder held in place by a glass matrix. In this embodiment, since each particle constituting the ruthenium compound powder is an acicular particle, a conductive network in the major axis direction and a conductive network in the minor axis direction are formed in each ruthenium compound powder. When a current is applied to a thick-film resistor having such a structure during pulse trimming, the glass matrix around the conductive network is heated and remelted, causing a shift in the arrangement of each particle constituting each ruthenium compound powder constituting the conductive network in the major axis direction, and the conductive network is reconstructed. This reconstruction of the conductive network changes the resistance value.

[0024] On the other hand, in a conductive network that is different from the present embodiment and has a ratio of the long axis to the short axis in the cross section (long axis in the long axis direction / short axis in the cross section) of less than 1.5 and is composed only of granular ruthenium compound powder, even if the conductive network is reconstructed after current is applied during pulse trimming, the deviation in the arrangement of the particles that compose each ruthenium compound powder is small and the change in resistance value is small.

[0025] The ruthenium compound powder is preferably contained in the thick film resistor composition in an amount of 5 mass % or more and 60 mass % or less, more preferably 10 mass % or more and 55 mass % or less, and even more preferably 15 mass % or more and 50 mass % or less.

[0026] In the thick-film resistor composition, the resistance value of the thick-film resistor obtained is adjusted by the mixing ratio of the glass frit and the ruthenium compound powder. If the content of the ruthenium compound powder contained in the thick-film resistor composition is less than 5 mass%, the resistance value becomes too high. On the other hand, if the content of the ruthenium compound powder contained in the thick-film resistor composition exceeds 60 mass%, the sintered surface of the thick-film resistor does not become dense, so that the mechanical strength of the thick-film resistor cannot be ensured.

[0027] The ruthenium compound constituting the powder is preferably ruthenium dioxide. This is because ruthenium dioxide has a lower resistivity than ruthenium composite oxides such as lead ruthenate, and is suitable for realizing a resistance value in the range of 50 Ω to 3000 Ω for thick-film resistors in the low resistance range. When using a thick-film resistor as a heating resistor, it is desirable to set the resistance value of the thick-film resistor to 50Ω to 100 kΩ, taking into consideration the pulse trimming characteristics and the power consumption of the resulting thick-film resistor.

[0028] An example of synthesis of the ruthenium compound powder of this embodiment will be described. One example of a method for producing ruthenium dioxide powder of acicular particles includes an acicular heat treatment step in which granular ruthenium dioxide powder is heat-treated in the presence of a bismuth compound to form acicular ruthenium dioxide powder, followed by a separation step in which the acicular ruthenium dioxide powder is separated into solid and liquid from a solution obtained by dissolving the bismuth compound in a solvent.

[0029] To explain the series of steps in detail, in the acicular heat treatment step, a first mixture prepared by mixing ruthenium dioxide powder and a bismuth compound is subjected to heat treatment to obtain a second mixture, which is then cooled to room temperature. The cooled second mixture is then subjected to a separation step in which the second mixture is dissolved in an acid or the like to obtain acicular ruthenium dioxide powder by solid-liquid separation.

[0030] The granular ruthenium dioxide powder is preferably spherical or nearly spherical particles having an average primary particle size of 100 nm or less as observed using an SEM and an aspect ratio of the powder of less than 1.5. When ruthenium dioxide powder having such a shape is used as a raw material, needle-shaped ruthenium dioxide powder having a maximum width of 100 nm or less in a cross section perpendicular to the particle length direction can be easily obtained.

[0031] The bismuth compound is a compound containing bismuth, and any known bismuth compound can be used as long as it does not form an alloy with ruthenium dioxide during heat treatment. The bismuth compound may be, for example, bismuth chloride, bismuth oxychloride, bismuth oxide, a mixture thereof, etc. Among them, it is preferable to use at least one of bismuth chloride and bismuth oxychloride, and it is more preferable to use bismuth oxychloride.

[0032] The first mixture is obtained by mixing the granular ruthenium dioxide powder and the bismuth compound. The mixing ratio of the granular ruthenium dioxide powder and the bismuth compound is, for example, 0.1 to 5 times, preferably 0.5 to 3 times, and more preferably 0.5 to 2 times, in terms of the molar ratio of the bismuth compound to the granular ruthenium dioxide powder.

[0033] The method for mixing the granular ruthenium dioxide powder and the bismuth compound is not particularly limited as long as the two can be mixed sufficiently, and they can be mixed using a known mixing device, such as a ball mill, a mortar and pestle mixer, or a shaker mixer.

[0034] The acicular heat treatment step can be carried out in an oxidizing atmosphere at a temperature of 600° C. to 900° C. By adjusting the heat treatment temperature within the above range, the particle length (L) and thickness (maximum width φ1 of the cross section perpendicular to the particle length direction) of the obtained acicular particles of ruthenium dioxide powder can be easily controlled. The conditions of this heat treatment can be appropriately adjusted depending on the types and shapes of the raw material granular ruthenium dioxide powder and the bismuth compound, as well as the mixing ratio, within a range in which acicular ruthenium dioxide powder can be obtained. For example, the heat treatment can be performed in an oxidizing atmosphere, such as an air atmosphere. The oxidizing atmosphere refers to a gas containing 10% or more by volume of oxygen, and for example, air can be used. The heat treatment time is not particularly limited, and can be, for example, from 1 hour to 4 hours, and is preferably from 1 hour to less than 3 hours.

[0035] In the separation step, the bismuth compound contained in the second mixture (mixed powder containing acicular ruthenium dioxide powder and a bismuth compound) is dissolved in a solvent, and then the acicular ruthenium dioxide powder is subjected to solid-liquid separation from the resulting solution. The solvent used to dissolve the bismuth compound is not particularly limited as long as it dissolves only the bismuth compound without dissolving the ruthenium dioxide powder, and for example, an acid of an inorganic compound (mineral acid) or an organic acid can be used. The conditions for dissolving the bismuth compound in the solvent are not particularly limited, and it is sufficient that the bismuth compound is sufficiently dissolved in the solvent. For example, the liquid temperature during dissolution can be about 30 to 60°C.

[0036] After dissolving the bismuth compound in the solvent, the ruthenium dioxide powder of acicular particles is dispersed, and a solution containing the dissolved bismuth compound is obtained. From the obtained solution, the ruthenium dioxide powder of acicular particles can be obtained through a solid-liquid separation process. The ruthenium dioxide powder of acicular particles obtained by solid-liquid separation may be further dried, and the drying temperature and time may be any temperature that can remove moisture.

[0037] Acicular ruthenium composite oxide powders, such as strontium ruthenate powder (SrRuO3) having acicular particles, can be obtained by mixing a solution of a chelate compound of a metal element other than ruthenium that constitutes a ruthenate salt such as strontium with acicular ruthenium dioxide powder to prepare a mixed liquid, drying the mixed liquid to gel it, thereby obtaining a chelate complex gel, and heat-treating the chelate complex gel at a temperature of 800°C or less.

[0038] [Thick film resistor composition] The thick-film resistor composition according to the present embodiment contains glass frit and ruthenium compound powder. In addition, the thick-film resistor composition may contain a known TiO2 powder or the like, which has an effect of adjusting the temperature coefficient of resistance, which is one of the electrical properties of the thick-film resistor.

[0039] [Organic vehicle] The organic vehicle used in this embodiment does not need to be a specific one, and may be one generally used for manufacturing thick-film resistor paste. It is preferable that the organic vehicle is one that volatilizes and decomposes when the binder is removed during drying and firing. The following organic solvents can be used, for example, cellulose-based resins such as ethyl cellulose and nitrocellulose, and resins such as acrylic resins.

[0040] These resins can be dissolved in organic solvents such as terpene alcohols such as terpineol, terpenes such as limonene, ethers such as butyl carbitol acetate and butyl cellosolve acetate, etc., and these organic solvents can be used as organic vehicles. To adjust the viscosity of the thick-film resistor paste, an organic solvent such as terpineol may be further added. In order to disperse the thick film resistor composition in the vehicle, a polymer dispersant having a carboxyl group or an amino group, a fatty acid such as stearic acid, or a phospholipid such as lecithin may be added as a dispersant.

[0041] [Thick film resistor paste manufacturing method] It is desirable to disperse the ruthenium compound powder, glass frit, organic vehicle, and organic solvent uniformly. There is no limitation on the method, but a known dispersion method using a three-roll mill is suitable.

[0042] [Method of forming thick film resistors] The resulting thick-film resistor paste is screen-printed onto a ceramic substrate such as an alumina substrate in the form of a thick-film resistor pattern, which is then dried and fired to form a thick-film resistor.

[0043] The firing conditions are a peak temperature of 800°C to 900°C in air, with the peak temperature held for 5 to 60 minutes. The heating time from room temperature to the peak temperature is also 5 to 60 minutes, and after holding the peak temperature, it is cooled to room temperature. When the temperature is raised during the firing process, a debindering process is performed to remove any organic solvents or resin components remaining in the printed film of the thick film resistor paste. The thick-film resistor fired at a peak temperature of 800° C. to 900° C. has a thickness adjusted to 5 μm to 20 μm, and more preferably 8 μm to 15 μm.

[0044] Furthermore, the surface of the thick-film resistor can be covered with a glass paste that can be fired at a firing temperature of about 600°C, and the glass paste can be fired to form a protective film for the thick-film resistor, thereby making it possible to produce a thick-film resistor with a protective film. By providing the surface of the thick-film resistor with a protective film made of glass paste in this way, the surface of the thick-film resistor can be made smooth. Prior to the formation of the thick film resistor, electrodes that will become the terminals of the thick film resistor may be formed on the surface of the ceramic substrate by a known thick film technique.

[0045] [Pulse trimming of thick film resistors] The resistance value of the thick-film resistor obtained by firing is adjusted by a pulse trimming method. Specifically, a pulse voltage is applied to the thick-film resistor until a predetermined resistance value is reached. The applied voltage may be appropriately selected depending on the resistance value of the thick-film resistor. If the rate of change in the resistance value after application of the pulse voltage is small compared to the resistance value before application when the pulse voltage is applied successively, it becomes difficult to efficiently adjust the resistance value. EXAMPLES

[0046] The present embodiment will now be described in detail with reference to examples. EXAMPLES

[0047] A thick-film resistor composition consisting of 13 mass% ruthenium dioxide powder A of acicular particles, 50 mass% lead aluminoborosilicate glass frit B, and the remainder an organic vehicle was kneaded in a three-roll mill so that the various inorganic materials constituting the composition were dispersed in the organic vehicle, producing the thick-film resistor paste of Example 1. Terpineol in which ethyl cellulose had been dissolved was used as the organic vehicle.

[0048] The ruthenium dioxide powder A used had a maximum cross-sectional width φ1 perpendicular to the particle length direction of 25 nm and an aspect ratio of 2.0, calculated from the particle length L and maximum width φ1 by the formula "particle length (L) / maximum width in cross section (φ1)". The particle length (L) and maximum cross-sectional width (φ1) of the ruthenium dioxide powder A with acicular particles were observed using TEM images.

[0049] Glass frit B had a 50% volume cumulative particle size of 1.3 μm and a softening point of 860°C. The organic vehicle was prepared by mixing 85% by mass of terpineol and 15% by mass of ethyl cellulose and dissolving them at 80°C.

[0050] [Method of forming thick film resistors] The thick-film resistor paste was printed with a width of 0.3 mm between five pairs of thick-film Au electrodes with a spacing of 0.3 mm that had been formed on an alumina substrate in advance, and dried in a belt furnace at a peak temperature of 150°C for 5 minutes to remove the solvent component terpineol. After that, it was fired in a belt furnace at a peak temperature of 810°C for 9 minutes. Five samples were prepared in the same manner, one per alumina substrate. The film thickness was measured by selecting one of the samples for evaluation at random per alumina substrate using a stylus-type surface roughness meter (Tokyo Seimitsu Co., Ltd., model number: Surfcom 480B), and the average film thickness of the five thick-film resistors was 13 μm.

[0051] Further, glass paste AP5564 manufactured by AGC was applied so as to cover the thick film resistor, and dried in a belt furnace at a peak temperature of 150°C for 5 minutes, and then fired in a belt furnace at a peak temperature of 810°C for 9 minutes to obtain an evaluation sample.

[0052] [Pulse trimming of thick film resistors] The resistance value Rs of the thick film resistor of the evaluation sample was measured before voltage application. Then, using "ESS-6008 (manufactured by Noise Laboratory Co., Ltd.)", the thick film resistor of the evaluation sample was applied with a capacitance of 200 pF, an internal resistance of 0 Ω, and a voltage of 1500 V, and each voltage pulse was applied to the thick film resistor of the evaluation sample. After that, a voltage pulse of 1500 V was applied again after a 1 second interval, and the resistance value Re after the voltage application was measured. The resistance change rate was calculated using the following formula (1). Table 1 shows the applied voltage and the calculated resistance change rate at that time. The resistance value was measured using a digital multimeter (KEITHLEY, No. 2001).

[0053]

number

[0054] Comparative Example 1 A thick-film resistor composition consisting of 11% by mass of ruthenium dioxide powder C of roughly spherical granular particles, 2% by mass of granular lead ruthenate powder D, 45% by mass of alumina borosilicate lead glass frit E, and the remainder being the same organic vehicle as in Example 1, was kneaded by a three-roll mill so that the various inorganic materials constituting the composition were dispersed in the organic vehicle, to prepare a thick-film resistor paste of Comparative Example 1. The granular ruthenium dioxide powder C used had a maximum width (φ1) of 20 nm in a cross section perpendicular to the direction of the particle length, and an aspect ratio of 1.1. The particle length (L) and maximum width (φ1) of the ruthenium dioxide powder were observed by TEM images, as in Example 1.

[0055] Lead ruthenate powder D was observed in a TEM image and was an approximately spherical powder with a maximum width (φ1) of 50 nm in a cross section perpendicular to the particle length direction, and an aspect ratio of 1.1, calculated by the particle length (L) and the maximum width (φ1). Glass frit E had a 50% volume cumulative particle size of 1.4 μm and a softening point of 660°C.

[0056] Further, thick-film resistors for evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 1. The film thickness of each of the five thick-film resistors was measured, and the average value of the five thick-film resistors was 8.6 μm.

[0057] [Table 1]

[0058] As shown in Table 1, the thick film resistor of Example 1 formed from the thick film resistor paste made using the acicular ruthenium dioxide powder of this example had a larger negative rate of resistance change in the pulse trimming evaluation than the thick film resistor of Comparative Example 1 formed from the conventional thick film resistor paste made using granular ruthenium dioxide powder, demonstrating superior pulse trimming properties. [Explanation of symbols]

[0059] 1 Ruthenium compound powder L particle length φ1 Maximum width of cross section

Claims

1. Contains glass frit and ruthenium compound powder, The ruthenium compound powder is an acicular particle, the maximum width of a cross section perpendicular to the particle length direction is 100 nm or less, and the ratio "particle length (L) / maximum width (φ)" calculated from the particle length and the maximum width is 1 The aspect ratio represented by the formula (2) is 1.5 or more and 5.0 or less, The thick film resistor composition is characterized in that the glass frit has a softening point of 600°C or more and 900°C or less, which is a peak temperature at which a differential thermal curve next to a temperature at which a decrease in a differential thermal curve on the higher side appears when the differential thermal curve obtained by heating the glass frit at a temperature increase rate of 10°C / min in air by differential thermal analysis (TG-DTA).

2. 2. The thick film resistor composition according to claim 1, wherein the ruthenium compound powder is ruthenium dioxide powder.

3. 3. A thick-film resistor paste comprising the thick-film resistor composition according to claim 1 or 2 and a vehicle in which a resin is dissolved in an organic solvent.

Citation Information

Patent Citations

  • Heating resistor for thermal print head, thermal print head, and method of manufacturing the heating resistor

    JP2002067366A

  • Thermal printing head, heating resistor used in the same, and method of manufacturing the heating resistor

    JP2002127483A

  • Thick film resistor composition and thick film resistor paste containing the same

    JP2019040782A